Marine scientific research : a revised guide to the implementation of the relevant provisions of the United Nations Convention on the Law of the Sea. (United Nations, 2010)
The present guide includes practical guidance on the implementation of the provisions of the Convention on the Law of the Sea relating to marine scientific research based on the outcome of the meeting of the Group of Experts. The General Assembly of the United Nations has highlighted the importance of marine science for eradicating poverty, contributing to food security, conserving the world's marine environment and resources, helping to understand, predict and respond to natural events and promoting the sustainable development of the oceans and seas.--Publisher's description.